Sifat fisika dan analisis gugus fungsi karet seal o-ring dari bahan termoplastik elastomer nitrile butadiene rubber (NBR) dan polyvinyl chloride (PVC) - Arum Yuniari; Nursamsi Sarengat (Majalah Kulit, Karet, dan Plastik, 2013)
ABSTRACTThe purpose of this research was to determine the physical properties and functionalgroups on O-ring rubber seals made of thermoplastic elastomers blend NBR and PVC.Composition of the NBR / PVC were successively varied : 90/10; 85/15; 80/20; 75/25; 70/30 and65/35 phr. Mixing process between NBR/PVC with additive used a two roll mill within atemperature of 60º - 80 ºC, the vulcanization process used a hydraulic press at a temperature of170 oC and pressure of 150 kg/cm2. The physical properties were evaluated including tensilestrength, elongation at break, hardness, before and after aging, hardness after immersion inisooctane and swelling while analysis of functional groups was also carried out by method ofFourier Transform Infrared Spectrophotometer (FTIR). The result of the best vulcanized wascharacterized by tensile strength 188.93 kg/cm2, the change of tensile strength after aging 2.50%,elongation at break of 400%, the change of elongation at break after aging was 12.5%, hardness75 shore A, the change of hardness after aging 0%, the change of hardness after immersion inisooctane 1.3%, swelling 0.8% and functional group of vulcanisate was indicated by new peak(OH) at wave band of 3468 cm-1. Those formula met the requirements of the technicalspecifications of ASTM D 2000 seal O-ring.Keywords: O-ring rubber seals, NBR, PVC, physical properties, functional groupABSTRAKTujuan penelitian ini adalah untuk mengetahui sifat fisika dan gugus fungsi karet seal Oringyang dibuat dari bahan termoplastik elastomer campuran NBR dan PVC. KomposisiNBR/PVC divariasi berturut-turut 90/10; 85/15; 80/20; 75/25; 70/30 dan 65/35 phr.Pencampuran NBR/PVC dengan bahan tambahan (aditive) menggunakan two roll mill pada suhu60º-80ºC, proses vulkanisasi menggunakan hydraulic press pada suhu 170 ºC dan tekanan 150kg/cm2. Pengujian sifat fisika karet seal O-ring meliputi tegangan putus, perpanjangan putus,kekerasan sebelum dan sesudah aging, kekerasan setelah perendaman dalam isooktan, swellingdan dilakukan juga analisis gugus fungsi dengan Fourier Transform Infrared Spectrophotometer(FTIR). Hasil uji vulkanisat terbaik sebagai berikut: tegangan putus 188,93 kg/cm2, perubahantegangan putus sesudah aging 2,50%, perpanjangan putus 400%, perubahan perpanjangan putussesudah aging 12,5%, kekerasan 75 shore A, perubahan kekerasan sesudah aging 0%, perubahankekerasan sesudah perendaman dalam isooktan 1,3%, swelling 0,8% dan muncul gugusfungsional baru OH pada bilangan gelombang 3468 cm-1. Karet seal O-ring tersebut memenuhipersyaratan ASTM D 2000 tentang spesifikasi teknis seal O-ring.Kata kunci: seal O-ring, NBR, PVC, sifat fisika, gugus fungsi